Palm Computing in 1994 - Glazer, Rashi; Asirvatham, B. J.; Mai, Tim; Mani, Narayana; Rogers, Paul (London : SAGE Publications Ltd, 2017)
In 1992, Palm Computing was founded to create add-on software for the emerging Personal Digital Assistant (PDA) market. Initial buyers of PDAs were often computer-savvy and enthusiastic about new technologies, and while industry analysts and the press expected PDAs to be the next trend in computing, many offerings failed as badly as earlier pen computers. By working with many different PDA vendors, Palm gained experience with the strengths and weaknesses of PDA products then on the market. Many Palm employees used (or, at least, tried to use) PDA products themselves. Users of Palms add-on software provided valuable feedback about what they wanted and did not want in a PDA. Palm then developed the Pilot device, and the next task was to create an equally solid marketing plan.
Originally published in Glazer, R., Asirvatham, B. J., Mai, T., Mani, N., & Rogers, P. (2000). Palm Computing in 1994. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Palm Computing (Firm); Marketing -- Management; Product management; New products; Computer software